OP0170 Treatment of Axial Spondyloarthritis with an Optimal Dosage of Nsaids: A 6-Week Follow Up Study Focusing on Magnetic Resonance Imaging of the Sacroiliac Joints. (9th June 2015) - Varkas, G.; Cypers, H.; Van Praet, L.; Jans, L.; Carron, P.; Elewaut, D.; van den Bosch, F.
Abstract : Background: In contrast to the established efficacy of anti- tumor necrosis factor α (TNFα) on BME of the sacroiliac joints (SIJ) (and spine), surprisingly little information exists on the impact of NSAIDs. As NSAID therapy was already the cornerstone of treatment before magnetic resonance imaging of the SIJ was introduced, very limited data on the effect of optimal NSAID therapy on the extent of inflammation, quantified by a validated score such as the Spondyloarthritis Research Consortium of Canada (SPARCC) scoring system, has been published. Our goal was therefore to examine the impact of NSAID use on disease activity and BME in an inception cohort of new onset AxSpA. Objectives: To evaluate the impact of full dose NSAIDs on the extent and intensity of bone marrow edema of the sacroiliac joints on magnetic resonance imaging in axial spondyloarthritis (AxSpA). Methods: A single center, 6-week study in a consecutive cohort of patients with clinical suspicion of AxSpA. A total of 102 patients were screened. Thirty- six patients with diagnosis of AxSpA and positive MRI SIJ were included for a follow-up MRI after 6 weeks of optimal dose of NSAIDs. Disease activity was monitored by a BASDAI questionnaire every 2 weeks and BASFI at baseline and week 6. NSAID intake was assessed by the ASAS NSAID- index. Primary endpoints were BASDAI response and improvement of the Spondyloarthritis Research Consortium of Canada (SPARCC) score of MRI SIJ at week 6. Results: About 38.5% of AxSpA patients was unable to continue the full dose NSAID schedule. Sixteen patients abided completely by the protocol. Median NSAID Index reached 97%. We calculated a mean decrease of 0.4 in BASDAI score per 2 weeks of therapy (P<0.001). Only 18.75% of patients (3/16) reached a BASDAI50 response at week 6. Overall, we found an 8% reduction in mean SPARCC scores at week 6 in comparison to baseline (P=0.046). Fifty percent of patients (8/16) displayed high intensity lesions on STIR at baseline, which decreased significantly at week 6 (P=0.043). Conclusions: We found a marginal decrease in bone marrow edema of the sacroiliac joints after 6 weeks of optimal NSAID therapy in newly presenting patients with axial spondyloarthritis and a high level of drop out in patients on NSAID therapy in addition to low BASDAI50 response. Disclosure of Interest: None declared